In situ vaccination with cowpea mosaic virus elicits systemic antitumor immunity and potentiates immune checkpoint blockade. Issue 12 (2nd December 2022) - Mao, Chenkai; Beiss, Veronique; Ho, Gregory W; Fields, Jennifer; Steinmetz, Nicole F; Fiering, Steven
Abstract : Background: In situ vaccination (ISV) is a cancer immunotherapy strategy in which immunostimulatory reagents are introduced directly into a tumor to stimulate antitumor immunity both against the treated tumor and systemically against untreated tumors. Recently, we showed that cowpea mosaic virus (CPMV) is a potent multi-toll-like receptor (TLR) agonist with potent efficacy for treating tumors in mice and dogs by ISV. However, ISV with CPMV alone does not uniformly treat all mouse tumor models tested, however this can be overcome through strategic combinations. More insight is needed to delineate potency and mechanism of systemic antitumor immunity and abscopal effect. Method: We investigated the systemic efficacy (abscopal effect) of CPMV ISV with a two-tumor mouse model using murine tumor lines B16F10, 4T1, CT26 and MC38. Flow cytometry identified changes in cell populations responsible for systemic efficacy of CPMV. Transgenic knockout mice and depleting antibodies validated the role of relevant candidate cell populations and cytokines. We evaluated these findings and engineered a multicomponent combination therapy to specifically target the candidate cell population and investigated its systemic efficacy, acquired resistance and immunological memory in mouse models. Results: ISV with CPMV induces systemic antitumor T-cell-mediated immunity that inhibits growth of untreated tumors and requires conventional type-1 dendritic cells (cDC1s). Furthermore, using multiple tumor mouse models resistant to anti-programmed death 1 (PD-1) therapy, we tested the hypothesis that CPMV along with local activation of antigen-presenting cells with agonistic anti-CD40 can synergize and strengthen antitumor efficacy. Indeed, this combination ISV strategy induces an influx of CD8 + T cells, triggers regression in both treated local and untreated distant tumors and potentiates tumor responses to anti-PD-1 therapy. Moreover, serial ISV overcomes resistance to anti-PD-1 therapy and establishes tumor-specific immunological memory. Conclusions: These findings provide new insights into in situ TLR activation and cDC1 recruitment as effective strategies to overcome resistance to immunotherapy in treated and untreated tumors.